A Study on Lean Manufacturing Implementation in Malaysian Automotive Component Industry - A. N. M., Rose; B. M., Deros; M. N., Ab. Rahman (Universiti Malaysia Pahang, 2013)
Lean manufacturing is an extended version of the Toyota Production System (TPS). It was highlighted as the best practice in the 21st century. Therefore, top and senior management in manufacturing firms are encouraged to adopt and adapt lean principles and practices in running their respective firms. The main objective of this paper is to investigate the extent of lean manufacturing perception and implementation in the Malaysian automotive component industry. A survey questionnaire was developed to collect top and senior management views with respect to their perception, judgement and opinion on twenty four lean manufacturing (LM) practices. This preliminary survey was conducted at 30 Malaysian automotive component manufacturing firms. The survey results show that a large majority of respondents have a high perception of the importance of lean manufacturing practices. However, it was found that their actual LM implementation is still on the low side. In this study, the non-parametric test was used to analyze the level of perception and implementation of the twenty four LM practices. The analysis of the survey results revealed that there are significant differences between the level of perception of the importance of LM practices and their actual implementation.